Assessment of knowledge, attitude, and factors associated with junk food consumption among medical student in Pokhara, Nepal: A cross-sectional study - Paudel, Sharmila; Poudel, Binita; Bastola, Sanju (Journal of Chitwan Medical College, 2025)
Introduction: Junk foods are readily available, usually inexpensive, and have less nutrient value. College life is a crucial time when they are especially vulnerable to acquire unhealthy eating habits. This study aims to assess junk food consumption among medical students in Pokhara. Methods: A cross-sectional study was conducted among 240 MBBS students of Gandaki Medical College from Nov to Dec 2023 using a self-administered questionnaire. Ethical approval was obtained. Simple random sampling was used. Chi-square test was used for the association between independent variables (age, sex of the respondent, type of family, current living status, study year, enabling environment (grocery and hotel near college and house) and junk food consumption. A p-value ≤0.05 was considered statistically significant. Results: The prevalence of junk food consumption among the medical student was 223(92.9% of 240) The study surveyed 121(50.4%) of the respondents who had adequate knowledge of junk food consumption. More than half 146(60.8%) of the respondents had a low attitude toward junk food consumption. A study found that current living status (p=0.01), and type of family (p=0.02) were found to be significantly associated with junk food consumption. Conclusion: Junk food consumption was common among undergraduate students. The living status, like currently living in rent or hostel had higher consumption of junk food compared to those respondents who live with their family.